2017
DOI: 10.1111/trf.14298
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing blood donor skin disinfection using natural oils

Abstract: The anti-biofilm activity of chlorhexidine-gluconate plus isopropyl alcohol can be greatly enhanced by L. multifida oil or linalool. Therefore, these components could potentially be used to improve blood donor skin disinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…They showed that in biofilm, CHD combined with eucalyptus oil demonstrated synergistic activity against the clinical isolate of Staphylococcus epidermidis, with an FICI value of 0.19. According to Alabdullatif et al [26] linalool significantly enhances anti-biofilm activity of CHD with isopropyl alcohol and can potentially be used to improve skin disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that in biofilm, CHD combined with eucalyptus oil demonstrated synergistic activity against the clinical isolate of Staphylococcus epidermidis, with an FICI value of 0.19. According to Alabdullatif et al [26] linalool significantly enhances anti-biofilm activity of CHD with isopropyl alcohol and can potentially be used to improve skin disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…In traditional medicine and in clinical practice, T. vulgaris is used, and T. vulgaris shows promising results on inflammatory skin disorders [ 115 ], scabies, herpes, wounds, alopecia, dental plaque [ 116 ], ringworm, and headaches [ 106 ]. Moreover, T. vulgaris showed a promising insecticidal effect on Culex pipiens , the vector for lymphatic filariasis [ 117 ], demonstrating an increased importance in many fields.…”
Section: Species Of the Lamiaceae Family With Potential Analgesic/mentioning
confidence: 99%
“…The presumptive drug target of MRSA biofilm is dehydroxysqualene synthase which produces staphyloxanthin, its main biofilm component [162, 163, 164, 53, 115]. Essential oils are also used to treat infections against gram negative bacteria relevant in veterinary in the Syn-NPs-CAAs format [5].…”
Section: Resultsmentioning
confidence: 99%
“…The presumptive drug target of MRSA biofilm is dehydroxysqualene synthase which produces staphyloxanthin, its main biofilm component [162,163,164,53,115].…”
Section: Inhibition Of Toxin Production and Antibiofilm Activitiesmentioning
confidence: 99%